(untitled) (Conferencea, 2022)
In the process of convective drying of chemical fertilizers, drum dryers are widely used, their simplicity of construction and high technical and economic indicators have ensured their widespread use in the industry compared to other types of dryers. The final results of their drying depend on the nature of the movement of the agents involved in the process, and the solutions of the material and heat balance equations in the process are determined by the hydrodynamics of the environment. The movement of currents in drum devices is extremely complex, and it is a difficult problem to mathematically model it and find exact solutions covering all aspects of the process. Therefore, the description of such processes is shown by various hydrodynamic models. Ignoring the movement properties of the material leads to an incorrect assessment of the hydrodynamic situation in the apparatus.